Ambiphilicity of a mononuclear cobalt(iii) superoxo complex. Issue 94 (5th November 2020) - Chen, Ting-Yi; Ho, Po-Hsun; Spyra, Can-Jerome; Meyer, Franc; Bill, Eckhard; Ye, Shengfa; Lee, Way-Zen
Abstract : Addition of HOTf to a mixture of Co III (BDPP)(O2 ˙) (1 ) and Cp*2 Fe produced H2 O2 in high yield implying formation of Co III (BDPP)(OOH) (3 ), and reaction of Sc(OTf)3 with the same mixture gave a peroxo-bridged Co III /Sc III 5 . Abstract : Addition of HOTf to a mixture of Co III (BDPP)(O2 ˙) (1, H2 BDPP = 2, 6-bis((2-( S )-diphenylhydroxylmethyl-1-pyrrolidinyl)methyl)pyridine) and Cp*2 Fe produced H2 O2 in high yield implying formation of Co III (BDPP)(OOH) (3 ), and reaction of Sc(OTf)3 with the same mixture gave a peroxo-bridged Co III /Sc III 5 . These findings demonstrate the ambiphilic property of Co III -superoxo 1 .